Frequency of gallstones in female healthcare workers of childbearing age in Malatya region (Annals of Medical Research, 2023)
Aim: Gallstones are seen more frequently in women and in both sexes in the society, causing serious health problems and reducing the quality of life. In this study, we aimed to evaluate and present the frequency of gallstones among female healthcare professionals of reproductive age in the Malatya region. This is the first study in our country in the field of gallbladder stone frequency among female healthcare professionals of childbearing age.Materials and Methods: We included all female employees of childbearing age working in our hospital, and the frequency of gallstones was found by retrospectively evaluating the routine records of healthcare professionals in the hospital. The frequency of gallstones in the patients was obtained from routine abdominal ultrasonography records made during health checks and abdominal tomography records when necessary. Frequency of data was used as number and percentage for statistical evaluation of data, and Fisher's chi-square test was used for evaluation of non-numerical data.Results: The average age of female employees of childbearing age is 30.02 ± 5.42 years and the age range is 19-50 years. Of 1224 healthcare workers, 65 (5.3%) had gallbladder stones and 1.6% had polyps, and 35 (2.8%) had a history of cholecystectomy. Only the difference between gallstone rates according to body weight was statistically significant (p0.05). In our cases, it was determined that gallstones increased in parallel with age and weight.Conclusion: As a result, the frequency of gallstones among female healthcare workers of reproductive age was statistically significantly proportional to body weight. The incidence of gallstones was directly proportional to weight, patient age, and working time in the hospital.
Keywords: Gallstones; Obesity; Healthcare workers